THE ROLE OF FORUMS IN ONLINE INSTRUCTION - Kadagidze, Lamara (European Scientific Journal, ESJ, 2014)
Student’s learning and teacher’s teaching could be enhanced by technology if used appropriately. Technology could encourage more independent and active learning among students. A key reason for the use of technology within a learning situation is to enhance the quality of learning and teaching. Computer-based online discussions or online forums have been used in a wide range of higher education setting to provide major learning environments for distance education or to supplement face-to-face discussionns. The article reviews the challenges and benefits of forums in online education and poses the issues of characteristics, integration, maximizing learning, controversy and the role of the instructor and administrator as a facilitator/participant within the discussion forum. It reveals several foreign studies regarding the topics and provides recommendations for potential users of the tool throughout the international arena of education. In order to foster an interactive learning community and encourage student interactions, all of the administrators, faculty, and staff in a distance education program need to collaborate with each other at an institutional level. Besides fostering common educational practices in conventional classrooms, distance education is portrayed as possessing more potential and thus more promise in promoting student interactions and enhancing learning outcomes by utilizing advanced computer technology.